2013
DOI: 10.1055/s-0032-1326009
|View full text |Cite
|
Sign up to set email alerts
|

S2K-Leitlinie zur Diagnostik und Therapie der idiopathischen Lungenfibrose

Abstract: Idiopathic pulmonary fibrosis is a fatal lung disease with a variable and unpredictable natural history and limited treatment options. Since publication of the ATS-ERS statement on IPF in the year 2000 diagnostic standards have improved and a considerable number of randomized controlled treatment trials have been published necessitating a revision. In the years 2006 - 2010 an international panel of IPF experts produced an evidence-based guideline on diagnosis and treatment of IPF, which was published in 2011. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 136 publications
0
12
0
16
Order By: Relevance
“…To be eligible for treatment and inclusions in our analyses, patients were required to have a confirmed multidisciplinary team diagnosis of IPF in accordance with the ATS/ERS/JRS/ALAT consensus guidelines [18] and the German guideline for diagnosis and treatment of IPF [19]. …”
Section: Methodsmentioning
confidence: 99%
“…To be eligible for treatment and inclusions in our analyses, patients were required to have a confirmed multidisciplinary team diagnosis of IPF in accordance with the ATS/ERS/JRS/ALAT consensus guidelines [18] and the German guideline for diagnosis and treatment of IPF [19]. …”
Section: Methodsmentioning
confidence: 99%
“…A Cochrane meta-analysis on the cumulative data of these phase II and III trials involving a total of 1,155 patients showed that pirfenidone slows down the decline of FVC and reduces the risk of disease progression by 30% [12]. Consequently, pirfenidone was given a weak positive treatment recommendation in the German guideline for the diagnosis and management of IPF [13]. In addition, the British National Institute for Health and Care Excellence (NICE) approved pirfenidone as a treatment option for mild-to-moderate IPF in a recent technology appraisal guidance [14].…”
Section: Introductionmentioning
confidence: 99%
“…A multidisciplinary team involved in IPF diagnosis should always include a clinician (pulmonologist) and radiologist as well as pathologist (in case of lung biopsy has been performed)all should be experienced in ILD diagnosis, and if needed, also a rheumatologist (possibility of CTD), occupational medicine specialist (potential environmental exposure), specialist in respiratory physiology, cardiologist (both helpful, for instance, in assessing the risk associated with invasive diagnosis) or another specialist whose assessment can be helpful in making diagnostic or therapeutic decisions [29,87,[201][202][203]. A MDD in IPF diagnosis is of greatest importance when there is no unequivocal radiographic diagnosis of UIP (in HRCT) [29,31,204].…”
Section: Question 7 What Is the Role Of A Multidisciplinary Team In mentioning
confidence: 99%
“…The involvement of a MDD is considered the gold standard in the diagnostic process for IPF, especially in differentiation from other ILDs associated with fibrosis [1,29,31,87,201]. An appropriate assessment of the HRCT image forms the basis of IPF diagnosis.…”
Section: Commentarymentioning
confidence: 99%